Penentuan prosedur efektif dalam menerapkan manajemen risiko operasional perbankan syariah - Pratama, Mohammad Aditya (Maliki Interdisciplinary Journal, 2024)
Risk management is an important tool in a banking institution. Risk management is a science that studies how an institution or organization can apply measures to map various kinds of problems in banking. The aim of this research is to find out the procedures and stages for carrying out risk management for banking operational risks. This research uses a qualitative method by conducting a literature study approach to previous research. The data in this type of research is secondary data, which means the data is obtained from literature studies in previous research. The results of this research were a procedure and stages in carrying out risk management for banking operational risks. Apart from that, this research also produces the forms and causes of operational risk in banking.